2005
DOI: 10.1074/jbc.m507658200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Y14 Modulates Its Interaction with Proteins Involved in mRNA Metabolism and Influences Its Methylation

Abstract: The multicomponent exon junction complex (EJC) is deposited on the spliced mRNA during pre-mRNA splicing and is implicated in several post-splicing events, including mRNA export, nonsensemediated mRNA decay (NMD), and translation control. This report is the first to identify potential post-translational modifications of the EJC core component Y14. We demonstrate that Y14 is phosphorylated at its repeated arginine/serine (RS) dipeptides, likely by SR protein-specific kinases. Phosphorylation of Y14 abolished it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 39 publications
3
64
1
Order By: Relevance
“…Plasmid Construction-The bacterial expression vectors encoding His-tagged human Y14 and Dcp2, and glutathione S-transferase (GST)-Y14 were described previously (22)(23)(24). The Y14 mutants (W73V, F76V, F93V, Y116V, Y121V, E122V, W148V, and F150V) were generated from pGEX-GST-Y14 by site-directed mutagenesis and were verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid Construction-The bacterial expression vectors encoding His-tagged human Y14 and Dcp2, and glutathione S-transferase (GST)-Y14 were described previously (22)(23)(24). The Y14 mutants (W73V, F76V, F93V, Y116V, Y121V, E122V, W148V, and F150V) were generated from pGEX-GST-Y14 by site-directed mutagenesis and were verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…In Vitro Pull Down Assay-In vitro pull down was performed essentially as described (23,24). PYM was in vitro translated and 35 S-labeled using the TNT-coupled transcription/translation system (Promega) and was incubated with 2 g of individual GST-fusion proteins (ϳ40 pmol) in a 50-l mixture for 30 min at 30°C followed by affinity selection with glutathioneSepharose (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that phosphorylation of the Y14 protein, another key component of the EJC, abolished its interaction with other EJC components as well as factors downstream of the EJC (Hsu et al, 2005). Therefore, it is possible that phosphorylation of eIF4AIII similarly disturbs its interaction with other EJC components, causing it to dissociate from the EJC and to diffuse into the cytoplasm, as we observed in the fry2-1 mutant.…”
Section: The Phosphorylation and Localization Of Eif4aiiimentioning
confidence: 42%
“…We have reported previously that the RG-rich sequences in the C-terminal domain of human Y14 can be methylated, and the RS dipeptides can be phosphorylated (6). In this study, our initial attempt to search for the enzymes or regulators responsible for post-translational modification of Y14 led to the identification of the protein-arginine methyltransferase PRMT5 as a potential interacting factor of Y14.…”
mentioning
confidence: 99%
“…Y14 contains an RNA recognition motif in the central region, which is involved in the interaction with its stable partner Magoh (5). The C-terminal region of Y14 harboring two consecutive arginine-serine (RS) dipeptides and several arginine and glycine residues is predicted to be less structured but can be post-translationally modified (6). In Drosophila, the Y14/Mago homolog participates in transport and translation control of posterior mRNAs during oogenesis (7,8).…”
mentioning
confidence: 99%